2020
DOI: 10.3390/vaccines8020232
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Adverse Effects in Cultured Neuroblastoma 2A (N2A) Cells Duplicate Toxicity of Serum from Patients with Gulf War Illness (GWI) and Are Prevented in the Presence of Specific Anti-Vaccine Antibodies

Abstract: Gulf War illness (GWI) is a chronic disease of unknown etiology affecting over 200,000 veterans with symptoms including neurocognitive problems. We previously demonstrated GWI serum toxicity on neural cell cultures manifested by compromised neural network function, decreased cell spreading, and enhanced cell apoptosis. These patients lacked six human leukocyte antigen (HLA) class II alleles, resulting in an inability to form antibodies. Therefore, we hypothesized that GWI patients have vaccine-derived, persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Neuroinflammation and cognitive disorders induced likely by GW chemicals are observed to be the most commonly occurring symptoms of veterans with GWI [3,39]. We and others have found that neuroinflammation in GWI mouse models causes increased expression of pro-inflammatory cytokine such as IL-1β, IL-6, TNF-α, and DAMPs like HMGB1 in the brain, damaged blood-brain barrier (BBB) through alteration of tight junction protein, decreased expression of neuronal plasticity markers, and activation of TLR4 in the brain [6,10,40,41]. Results showed that SsnB exposure significantly decreased elevated expression of HMGB1 and IL-1β in GW groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroinflammation and cognitive disorders induced likely by GW chemicals are observed to be the most commonly occurring symptoms of veterans with GWI [3,39]. We and others have found that neuroinflammation in GWI mouse models causes increased expression of pro-inflammatory cytokine such as IL-1β, IL-6, TNF-α, and DAMPs like HMGB1 in the brain, damaged blood-brain barrier (BBB) through alteration of tight junction protein, decreased expression of neuronal plasticity markers, and activation of TLR4 in the brain [6,10,40,41]. Results showed that SsnB exposure significantly decreased elevated expression of HMGB1 and IL-1β in GW groups.…”
Section: Discussionmentioning
confidence: 99%
“…The prescribed drug used in our model is Pyridostigmine Bromide (PB). It is worth noting that not one model is a perfect platform for investigating GWI pathogenesis since exposures during that time period varied widely [5,36,40,41]. The use of an insecticide such as Permethrin is representative of the harmful effects of these classes of compounds [3].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence from human [18][19][20][21] , in vitro [22][23][24][25][26] , and in silico 27 studies implicates persistent antigens stemming from lack of immunogenetic protection in GWI and GWassociated inflammation. Specifically, six Class II human leukocyte antigens (HLA), which play an essential role in host protection via antibody production, have been shown to distinguish healthy GW veterans from those with GWI, and the number of these protective HLA alleles corresponds with GWI symptom severity in a dose dependent manner 18 .…”
Section: Gwi: Lack Of Immunogenetic Protectionmentioning
confidence: 99%
“…We have speculated that persistent foreign antigens from vaccines administered to Gulf War veterans lacking immunogenetic protection against them may underlie GWI. To that end, in vitro studies have demonstrated harmful effects of serum from GWI veterans on neural cultures that is ameliorated with serum from healthy Gulf War veterans 22 , pooled antibodies 23 , and antibodies against Gulf War vaccine antigens [24][25][26] .…”
Section: Gwi: Lack Of Immunogenetic Protectionmentioning
confidence: 99%
“…Side effects of influenza vaccine have been reported in vivo, and in vitro experiments indicate toxicity of this vaccine leading to compromised cell structure and function, resulting in apoptosis [ 12 ]. Vaccine antigens can be harmful to several cell functions; for example, the anthrax vaccine contains a protective antigen that compromises plasma membrane integrity as well as cytoskeletal and mitochondrial function in neuronal cell cultures [ 13 ].…”
mentioning
confidence: 99%